Corduroy takes a bow - Davis, Viola, 1965-; Hennessy, B. G. (Barbara G.); Freeman, Don (Viking, 2018)
When Lisa takes Corduroy to the theater for the first time, Corduroy heads out on his own to explore the whole building, including the dressing rooms, orchestra pit, and prop table.